Customer Satisfaction Low Cost Carrier: Stimulus AndIts Consequences - Sri Vandayuli Riorini; Christina Catur Widayati (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2018)
Airline industries are currently faced with challenges to satisfy consumers in order to improve organizational performance. The purpose of this study is to analyze service quality, corporate image, price fairness, and airline safety as a stimulus of customer satisfaction and its impact on brand loyalty. Samples data of 350 Low Cost Carrier/LCC passengers in Indonesia were collected and purposive sampling technique was used to analyze the developed hypothesis. Further data is processed with Structural Equation Modeling technique. The results of the study found that the stimulus of customer satisfaction of LCC is service quality, corporate image, price fairness, and airline safety. Furthermore, customer satisfaction will provide consequences for airline brand loyalty. The study also found that corporate image is the strongest factor affecting customer satisfaction. For further research, it is suggested to add customer value as a stimulus of customer satisfaction.